2022
DOI: 10.5423/ppj.nt.01.2022.0009
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Visual Detection of Barley Yellow Dwarf Virus by Reverse Transcription Recombinase Polymerase Amplification with Lateral Flow Strips

Abstract: Barley yellow dwarf virus (BYDV) has been a major viral pathogen causing significant losses of cereal crops including oats worldwide. It spreads naturally through aphids, and a rapid, specific, and reliable diagnostic method is imperative for disease monitoring and management. Here, we established a rapid and reliable method for isothermal reverse transcription recombinase polymerase amplification (RT-RPA) combined with a lateral flow strips (LFS) assay for the detection of BYDV-infected oat samples based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…To date, there are a number of reports on the development of RPA-based assays for plant viruses ( Babu et al, 2018 ; Babujee et al, 2019 ; Kim et al, 2019 , 2020 , 2022 , 2016; Lu et al, 2018 ; Mekuria et al, 2014 ; Silva et al, 2014 ; Zhang et al, 2014 ) and viroids ( Hammond and Zhang, 2016 ; Ivanov et al, 2020 ; Kovalskaya and Hammond, 2022 ; Lee et al, 2020 ). The RT-RPA-LFI assays for detection of plant viruses and viroids were performed in accordance with the TwistDx kit and lateral flow strips were utilized as an end-point readout method ( Kim et al, 2022 ; Kovalskaya and Hammond, 2022 ). Most RPA assays were developed with a TwistAmp nfo kit which is required nfo probe as well as a specific primer set ( Babu et al, 2018 ; Ivanov et al, 2020 ; Kim et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are a number of reports on the development of RPA-based assays for plant viruses ( Babu et al, 2018 ; Babujee et al, 2019 ; Kim et al, 2019 , 2020 , 2022 , 2016; Lu et al, 2018 ; Mekuria et al, 2014 ; Silva et al, 2014 ; Zhang et al, 2014 ) and viroids ( Hammond and Zhang, 2016 ; Ivanov et al, 2020 ; Kovalskaya and Hammond, 2022 ; Lee et al, 2020 ). The RT-RPA-LFI assays for detection of plant viruses and viroids were performed in accordance with the TwistDx kit and lateral flow strips were utilized as an end-point readout method ( Kim et al, 2022 ; Kovalskaya and Hammond, 2022 ). Most RPA assays were developed with a TwistAmp nfo kit which is required nfo probe as well as a specific primer set ( Babu et al, 2018 ; Ivanov et al, 2020 ; Kim et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The RT-RPA-LFI assays for detection of plant viruses and viroids were performed in accordance with the TwistDx kit and lateral flow strips were utilized as an end-point readout method ( Kim et al, 2022 ; Kovalskaya and Hammond, 2022 ). Most RPA assays were developed with a TwistAmp nfo kit which is required nfo probe as well as a specific primer set ( Babu et al, 2018 ; Ivanov et al, 2020 ; Kim et al, 2022 ). Here, we validated RPA reaction for the detection of CymMV with a TwistAmp basic kit without a probe.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the primer labeled RPA-LFS method could detect 10 3 copies of RNA within 30 min, and its half-maximal binding concentration was 22 times lower than the probe-dependent RPA-LFS ( Ivanov et al., 2021 ). RPA could also detect tomato apical stunt viroid ( Kovalskaya and Hammond, 2022 ) and barley yellow dwarf virus ( Kim et al., 2022 ) in plants. The application of RPA in virus detection often required reverse transcription first.…”
Section: The Application Of Rpamentioning
confidence: 99%
“…Like most PoU methodologies RPA reactions are isothermal and therefore do not require expensive equipment such as thermocyclers, but unlike LFIA they can reach PCR-comparable levels of sensitivity as demonstrated by the newly developed tomato yellow leaf curl virus and tomato spotted wilt virus assays [ 56 , 57 ]. A lateral flow readout has been added to RPA systems for plant virus detection, whereby labelled amplicons bind to membrane-immobilised complementary probes [ 57 , 58 , 59 ]. This adaptation has also been integrated into another commonly used isothermal detection, loop mediated amplification (LAMP), for the detection of both RNA and DNA plant viruses [ 60 , 61 , 62 ].…”
Section: New and Old Technologiesmentioning
confidence: 99%